Unusual case of Lemierre's syndrome. Issue 1 (28th November 2018) - Jawad, Issrah I; Chandna, Arjun; Morris-Jones, Stephen; Logan, Sarah
Abstract : A young previously healthy patient presented with sepsis and cavitating pneumonia. Campylobacter rectus was isolated from blood cultures and subsequent CT neck showed an internal jugular vein thrombosis. Treatment was with antibiotics, anticoagulation and supportive management. Lemierre's syndrome is an infectious thrombophlebitis of the internal jugular vein. Although a rare diagnosis since the use of penicillin for treatment of acute pharyngitis, it is being reported with increasing frequency. Usually associated with Fusobacterium spp, we believe that this is the first reported case of Lemierre's caused by C. rectus— an anaerobic member of the human oral cavity flora, usually associated with localised periodontal disease. The bacillus was isolated from blood during the acute presentation.